The Burden of Diabetes-Related Chronic Kidney Disease in China From 1990 to 2019 - Pan, Xiaowen; Lin, Xiling; Huang, Xin; Xu, Jingya; Ye, Lingxia; Zhang, Tianyue; Hu, Shaoning; Jiang, Hongwei; Ren, Yuezhong; Shan, Peng-Fei (Frontiers in Endocrinology, 2022)
ABSTRACT Objective: To analyze the trends in disease burden of diabetes-related chronic kidney disease (CKD) by year, age, gender and types of diabetes in China from 1990 to 2019. Methods: Data on prevalence, deaths and disability-adjusted life years (DALYs) for diabetes-related CKD were extracted from the Global Burden of Disease (GBD) 2019 study. Analyses were performed by year, age, gender and types of diabetes. Results: In China, the numbers of deaths and DALYs of diabetes-related CKD continuously increased but the age-standardized rates (per 100,000 population) decreased over 30 years, in which the numbers of deaths and DALYs attributable to type 1 diabetes mellitus (T1DM)-related CKD barely changed and the age-standardized rates decreased over the years; and the number of deaths and DALYs attributable to type 2 diabetes mellitus (T2DM)-related CKD continuously increased, but the age-standardized rates also decreased. In 2019, 76.03 (58.24-95.61) thousand deaths and 2.13 (1.65–2.67) million DALYs were attributable to diabetes-related CKD, of which, T2DM accounted for 83.32% and 77.0% respectively, and T1DM accounted for the rest. Increasing gender disparity was seen, with males being more heavily impacted. The burden of diabetes-related CKD varied among different age groups, with the numbers of deaths and DALYs attributable to T1DM-related CKD peaking between 45 and 54 years of age and T2DM-related CKD peaking between 75 and 79 years of age; and the crude rates of deaths and DALYs attributable to T1DM-related CKD peaking between 70 and 79 years of age and 40 to 54 years of age, respectively, and T2DM-related CKD peaking over 90 years of age. Among neighboring and G20 countries, the burden of diabetes-related CKD in China was relatively controlled reflected by the ranking of adjusted death and DALYs rates. Conclusions: The burden of diabetes-related CKD in China worsens and shows gender disparities and different age distribution. Greater efforts are needed to improve the health outcomes of these patients, especially among males.